Stoichiometric homeostasis does not affect species dominance and stability in an alpine steppe, Tibetan Plateau - Wu, Jianbo; Wang, Xiaodan (Arctic, Antarctic, and Alpine Research, 2019)
Studies of stoichiometric homeostasis in different types of plant species growing in alpine steppe environments are important in understanding the fitness and nutrient-use strategies of alpine plants in northern Tibet, which may be correlated with species dominance and stability. We used an N- and P-addition experiment to investigate the stoichiometric homeostasis N (H-N) in the foliage of different plant species in the Stipa purpurea steppe of the Tibetan Plateau from 2013 to 2016. The concentration of N in the foliage of different types of plants increased significantly with the amount of N added. We found that the H-N value of the foliage of alpine steppe plants was much lower than that of plants in temperate grasslands and grasslands with tall grass, suggesting that these alpine plants can absorb more nutrients when they are available. There was no difference in the H-N values for different alpine plant species, which is also different from previously reported results for other types of grasslands. Furthermore, the temporal stability and dominance of species was not significantly correlated with the foliage H-N value of the species. Our results suggest that the H-N value of plant foliage in an alpine steppe environment little affected the species dominance and stability seen in the control and N-addition plots at the species level, which is in conflict with the results from temperate grasslands. The different types of species in this alpine steppe environment show the same nutrient utilization strategies (low H-N value, about 2) for coping with a variable and limited supply of nutrients.